2013
DOI: 10.1136/jech-2012-201761
|View full text |Cite
|
Sign up to set email alerts
|

Widening socioeconomic differences in mortality among men aged 65 years and older in Germany

Abstract: Widening socioeconomic mortality differences in Germany, especially in eastern Germany, show that population groups did not benefit equally from the improvements in survival. The results suggest that special efforts have to be taken in order to reduce mortality among people with lower socioeconomic status, especially in eastern Germany. Health equity should be considered a priority when planning policies, practices, and changes in the healthcare system and related sectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 20 publications
4
35
0
3
Order By: Relevance
“…Reducing socioeconomic inequalities in mortality critically depends upon speeding up mortality declines from cardiovascular diseases and other causes of death in lower socioeconomic groups. Recently, Kibele et al (2013) found similar results for Germany. 65-year-old men with the highest pension incomes could expect to live another 20 years, while 65-year-olds with the smallest pensions could expect to enjoy less than 15 years of additional life.…”
Section: The Mortality Transitionsupporting
confidence: 60%
“…Reducing socioeconomic inequalities in mortality critically depends upon speeding up mortality declines from cardiovascular diseases and other causes of death in lower socioeconomic groups. Recently, Kibele et al (2013) found similar results for Germany. 65-year-old men with the highest pension incomes could expect to live another 20 years, while 65-year-olds with the smallest pensions could expect to enjoy less than 15 years of additional life.…”
Section: The Mortality Transitionsupporting
confidence: 60%
“…Huisman [6] found that absolute measures of educational inequality in mortality increased well into old age in 11 European countries. Kibele et al [28] examined absolute and relative differences in mortality among men aged 65 years and older in Germany. The results showed that income inequalities in mortality rates and life expectancy persisted into old age and widened over time.…”
Section: Introductionmentioning
confidence: 99%
“…Spadek natężenia zgonów, a tym samym coraz dłuższe trwanie życia obserwowane jest od wielu lat nie tylko w Polsce, ale i na świecie (Crimmins, Beltrán--Sánchez, 2010;Kibele, Jasilionis, Shkolnikov, 2013;Krumholz i in., 2015).…”
Section: Wprowadzenieunclassified